IDENTIFICATION AND DENSITY OF MOSQUITO SPECIES THAT CAUSE FILARIASIS DISEASE IN TANIWEL WEST SERAM DISTRICT - Senen, Yan Berlin; Mose, Windi; Rehena, Johanis Fritzgal; Wael, Syahran (RUMPHIUS, 2023)
The purpose of this study was to look at the types and density of mosquitoes in the Taniwel district. Research time is August 2021. This research is descriptive in nature. where only see the type and density using the existing formula. In this study, Mansonia and Anopheles mosquitoes were found. The results showed that mosquitoes found in East Taniwel sub-district, Sohuwe Village, Lumahlatal, and Maloang found 2 genera of mosquitoes namely Mansonia and Anopheles with mansonia density in Sohuwe village 3.29%, Lumahlatan 2.83% and Maloang 2.66. while the density of Anopheles in Sohuwe village was 3.62%, Lumahlatan 3.45% and Maloang 2.66%.